Analisis kandungan mineral dalam air sumur air minum botol kemasan dan air isi ulang di kecamatan kemiling bandar lampung - Festy Ladyani Mustofa; Ismalia Husna; Devi Nilam Laila Safitri (Universitas Malahayati, 2022)
ABSTRACT Drinking water can be obtained through well water, bottled drinking water, and refill water which allows chemicals that are harmful to the body. therefore it is necessary to do research to determine the mineral content. Given the function of minerals cannot be replaced if a deficiency of one of these substances will cause abnormalities. To determine the mineral content of well water, bottled drinking water, and refill water in the District of Kemiling, Bandar Lampung. Descriptive research design. One sample of each type of water was taken and then given to the Sucofindo Bandar Lampung laboratory for mineral content analysis. For well water samples, it was necessary to boil them first before submitting them to the laboratory. In well water samples, bottled drinking water, and refillable water, the physical, chemical, and inorganic chemical parameters were below the quality standard set by the Minister of Health of the Republic of Indonesia through Permenkes No. 492 of 2010 concerning drinking water requirements. Analysis of mineral content in well water, bottled drinking water, and refillable water in the District of Kemiling Bandar Lampung fulfills the requirements for physical parameters, inorganic chemical parameters, and chemical parameters in the Minister of Health Regulation No.492 of 2010 concerning water requirements so that drink water could be safe for consumption. Keywords: Mineral, Drinking Water, Physical, Chemical, Inorganic ABSTRAK Air minum bisa didapatkan melalui air sumur, air minum botol kemasan dan air isi ulang yang memungkinkan terdapat bahan-bahan kimia yang berbahaya bagi tubuh. oleh karena itu perlu dilakukan penelitian untuk mengetahui kandungan mineral. Mengingat mineral tidak dapat digantikan fungsinya jika kekurangan salah satu zat tersebut akan menimbulkan kelainan. Tujuan untuk mengetahui kandungan mineral pada air sumur, air minum botol kemasan dan air isi ulang di Kecamatan Kemiling Bandar Lampung. Desain penelitian deskriptif. Masing-masing jenis air diambil satu sampel lalu diberikan kepada laboratorium Sucofindo Bandar Lampung untuk dianalisis kandungan mineral. Untuk sampel air sumur perlu dilakukan perebusan terlebih dahulu sebelum diserahkan kepada pihak laboratorium. Pada sampel air sumur, air minum botol kemasan dan air isi ulang jenis parameter fisik, kimia dan kimia anorganik berada di bawah baku mutu yang ditetapkan oleh Menteri Kesehatan Republik Indonesia melalui Permenkes No. 492/Menkes/Per/IV/2010 tentang persyaratan air minum. Analisis kandungan mineral dalam air sumur, air minum botol kemasan dan air isi ulang di Kecamatan Kemiling Bandar Lampung memenuhi syarat parameter fisik, parameter kimia anorganik, dan parameter kimia pada peraturan Menteri Kesehatan No. 492/MENKES/PER/IV/2010 tentang persyaratan air minum sehingga air minum dapat layak untuk dikonsumsi. Kata kunci : Mineral, Air Minum, Fisik, Kimia, Anorganik